FROM AWARENESS TO RHETORICAL CONTROL: STUDENT WRITERS’ HOOKS AND READER ENGAGEMENT IN ARGUMENTATIVE INTRODUCTIONS - Putri, Rahmadila Eka; Juitama, Reni; Nadine, Chelsea Aisyah (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2026)
This study investigates students’ strategic use of hooks and their perceptions of hooks as rhetorical strategies for enhancing reader engagement, highlighting the gap between conceptual understanding and rhetorical execution. Employing a descriptive quantitative design combined with text-based rhetorical analysis, this study examined the argumentative introductions of 20 applied undergraduate students alongside questionnaire data covering five metacognitive dimensions. The analysis showed an uneven distribution of hook types, dominated by question hooks (45%), followed by scenario (25%) and statistical hooks (15%), while general (10%) and provoking statements (5%) were minimally used, indicating a restricted and formulaic repertoire. Questionnaire results revealed consistently high mean scores, namely awareness (M = 2.78), selection strategy (M = 2.70), reader engagement (M = 2.73), reader orientation (M = 2.76), and writing reflection (M = 2.74), suggesting strong perceived awareness. However, item-level findings exposed key gaps where only 45% reported using varied hooks, 65% considered audience and purpose, and just 20% expressed confidence in writing introductions. These results indicated that students’ awareness remained largely declarative and procedural rather than strategic and flexible. Despite demonstrating relatively high rhetorical awareness, students still exhibited limited rhetorical control, constrained variation, partial audience orientation, and low confidence in constructing introductions. This finding emphasizes the necessity of explicit modeling, strategic variation, audience-oriented practice, and iterative feedback. Overall, the findings positioned student writers within a transitional phase from awareness toward rhetorical control, where metacognitive understanding had not yet fully transformed into effective rhetorical performance.